SERBUK BAMBU SEBAGAI ALTERNATIF BAHAN DASAR TINTA BRAILLE - dan Sri Lastuti, Erna Wiji Astuti, Fifit Astuti, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
The aims of this research are to find out the way to make proper compositionin making Braille ink using bamboo extract as an alternative basic material, toknow the quality of Braille ink using bamboo extract and to know the effectivenessof Braille ink made from bamboo extract to assist blind people in reading Brailleor Arabic letter like the normal one.This research belongs to an experimental research. The population of thisresearch was China ink.